'You Have to Integrate to Belong Here!': Acculturation and Exclusion among Turkish and Belgian Descent Students on a University Campus. (4th May 2022) - Colak, F. Zehra; Van Praag, Lore; Nicaise, Ides
ABSTRACT: While substantial attention has been given to the integration processes of ethnic minority groups across Western Europe, few studies have focused on how students in higher education engage with and make sense of these processes. We conducted qualitative semi-structured interviews with 25 female university students of Turkish and Belgian descent to shed light on students' acculturation meanings. Our analyses show that both student groups reiterate the mainstream interpretation of integration as an adaptation process targeting immigrants and their descendants, although their views differ particularly as they relate to the dimension of cultural maintenance. Students' accounts show how sweeping demands for integration are putting pressure on female ethnic minorities, restricting their freedom to negotiate their identities and making them vulnerable to exclusion and marginalisation. The acculturation attitudes of ethnic majority students, however, remain exclusionary as they fail to consider their own role in acculturation and enjoy few opportunities to build meaningful relations across ethnic groups on the university campus. We discuss the role of higher education context in reproducing such exclusionary mainstream integration discourses and delve further into the implications of gender in shaping students' acculturation meanings and experiences.